Internet of Things: Smart College - Swaroopa, PT; Chaitra, HK (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IoT) is the interconnection of uniquely identifiable embedded computing devices within the existing Internet infrastructure. Concept of smart college can one be of the emerging trend in IoT in coming up years where the thought of ‘Smart Campus, Secure Campus’ may become the new mantra. The vision of such an Internet Of Things (IoT) system, supported by private industries and governments globally will have the potential to mark an evolution in the way concept of education is viewed currently and will surely have a great impact on our environment and our lives. This paper hence provides an comprehensive thought and survey on enabling and using of IoT technologies in the educational institutions, Furthermore, the paper will present and discuss an idea about smart college using the concepts of IoT.